Influence of sire fertility status on conceptus-induced transcriptomic response of the bovine endometrium - O’Callaghan, E.; Sánchez, J.M.; Rabaglino, M.B.; McDonald, M.; Liu, H.; Spencer, T.E.; Fair, S.; Kenny, D.A.; Lonergan, P. (Frontiers in Cell and Developmental Biology, 2022)
The aim was to examine the effect of sire fertility status on conceptus-induced changes in the endometrial transcriptome. To generate elongated conceptuses, Day 7 blastocysts produced in vitro using frozen-thawed sperm from Holstein Friesian bulls (3 High fertility, HF and 3 Low fertility, LF) were transferred in groups of 5 to 10 to synchronized heifers (n=7 heifers per bull) and recovered following slaughter on Day 15. Day 15 endometrial explants recovered from the uterine horn ipsilateral to the corpus luteum were recovered from synchronized cyclic heifers (n=4). Explants from each heifer were co-cultured for 6 h in RPMI medium alone (Control) or with 100 ng/ml ovine recombinant interferon tau (IFNT) or with a single conceptus from each HF or LF bull. After 6 h, explants were snap frozen and stored at -80°C. Extracted mRNA was subjected to RNA-seq and the resulting data were analyzed with R software. The numbers of DEG (FDR<0.05) were: HF vs Control: 956; LF vs Control: 1021; IFNT vs Control: 1301; HF vs LF: 2. Unsurprisingly, the majority of DEG (658) were common to all comparisons and were related to IFNT production. Prior to applying the adjusted p-value, there were 700 DEG between HF and LF, with 191 and 509 genes more expressed in HF or LF, respectively (p<0.05). Overrepresentation analysis of KEGG pathways (FDR<0.05), revealed that DEG with higher expression in LF were involved in cell cycle and proteolysis. while those upregulated DEG by HF conceptuses were strongly associated with immune process pathways, such as TNF, NF-kappa B, cytokine-cytokine receptor interaction, and TLR signaling. These pathways were also enriched by DEG upregulated by IFNT compared to the Control. Furthermore, only the HF, and not the LF group, affected the expression of most genes in these pathways (p<0.05) according to a negative binomial regression model. Finally, a weighted gene co-expression network analysis revealed two clusters of co-expressed genes associated with the HF conceptuses (p<0.05), which were also enriched for the aforementioned pathways. In conclusion, HF conceptuses, similar to IFNT treatment, stimulated multiple pathways involved in immune response, which were apparently not affected by LF conceptuses.